Ectopic expression of a maize hybrid up-regulated gene, ErbB-3 binding Protein 1 (ZmEBP1), increases organ size by promoting cell proliferation in Arabidopsis. (February 2016) - Wang, Tianya; Sui, Zhipeng; Liu, Xinye; Li, Yangyang; Li, Hongjian; Xing, Jiewen; Song, Fangwei; Zhang, Yirong; Sun, Qixin; Ni, Zhongfu
Highlights: Among 4, 337 differentially expressed genes identified between hybrid Zong3/87-1 and its parental lines in immature ears at the floral organ differentiation stage, 4, 021 genes exhibited nonadditive expression patterns. The maize homolog of Arabidopsis EBP1, designated ZmEBP1, was upregulated in the immature ears of maize hybrids. Ectopic expression of ZmEBP1 in Arabidopsis increased organ size by promoting cell proliferation. Abstract: The alteration of gene expression in hybrids may be an important factor promoting phenotypic variation and plasticity. To provide insight into the underlying molecular basis of maize heterosis in terms of the kernel number per ear, we established DGE profiles for the immature ears of maize hybrid Zong3/87-1 and its parental lines at the floral organ differentiation stage. Among 4, 337 identified differentially expressed genes, 4, 021 (92%) exhibited nonadditive expression patterns in the hybrid. Notably, the maize homolog of Arabidopsis EBP1, designated ZmEBP1, displayed an overdominant expression pattern in the Zong3/87-1 hybrid. Moreover, the results of qRT-PCR revealed that the ZmEBP1 gene was upregulated in the immature ears of the reciprocal hybrids Zong3/87-1 and 87-1/Zong3 at different developmental stages. Additionally, ectopic expression of ZmEBP1 in Arabidopsis increased organ size, which was mainly attributed to an increase in cell numbers, rather than cell size. Considering all of these findings together, we speculate that upregulation of ZmEBP1 in maize hybrids may accelerate cell proliferation and promote ear development.